Characterization of minerals, metals, and materials 2014 : proceedings of a symposium sponsored by the Materials Characterization Committee of the Extraction and Processing Division of TMS (The Minerals, Metals, and Materials Society) ; held during the TMS 2014 143rd Annual Meeting & Exhibition, February 16-20, 2014, San Diego Convention Center, San Diego, California, USA - Carpenter, John S.; Bai, Chen-Guang; Hwang, Jiann-Yang; Ikhmayies, Shadia J.; Li, Bowen (Materials scientist); Monteiro, Sergio Neves; Peng, Zhiwei; Zhang, Mingming (Metallurgist) (Wiley, 2014)
This collection focuses on the characterization of minerals, metals, and materials as well as the application of characterization results on the processing of these materials. Focused sessions within the symposia include those centered on ferrous metals, non-ferrous metals, soft materials, ceramics, clays, composites, and minerals. In addition, sessions will focus exclusively on characterization concerns in the extraction, processing, and environmental application of materials. Finally, method development in characterization will be explored.